Epidemiology of cerebral palsy in Sumba Island, Indonesia. (20th July 2020) - Jahan, Israt; Al Imam, Mahmudul Hassan; Karim, Tasneem; Muhit, Mohammad; Hardianto, Denny; Das, Manik Chandra; Smithers‐Sheedy, Hayley; Badawi, Nadia; Khandaker, Gulam
Abstract : Aim: To define the epidemiology, clinical characteristics, and rehabilitation status of children with cerebral palsy (CP) in Sumba Island, Indonesia. Method: A community‐based key informant method survey among children (aged <18y) with CP was conducted between March and August 2017. Children with suspected CP underwent detailed neurodevelopmental assessment by a multidisciplinary medical team. Socio‐demographic characteristics, aetiology, motor type, motor severity, associated impairments, educational, and rehabilitation status were documented. Results: There were 130 children with clinically confirmed CP. The mean age at assessment was 8 years 11 months and 43.8% ( n =57) of the children were female. The mean age at CP diagnosis was 6 years 5 months. Of these children, 46.9% ( n =61) had post‐neonatally acquired CP, most frequently because of vaccine‐preventable infectious encephalopathy (73.8%, n =45). In total, 80.8% ( n =105) had a predominantly spastic motor type of CP and 83.8% ( n =109) were classified in Gross Motor Functional Classification System levels III to V. A total of 77.7% ( n =101) had at least one associated impairment (speech 77.5%, intellectual 29.2%, visual 13.8%, hearing 20.0%, and epilepsy 13.5%). And 66.2% ( n =86) had never received rehabilitation services. Interpretation: Post‐neonatally acquired CP was common in this setting. Addressing preventable post‐neonatally acquired risk factors for CP should be a public health priority. Earlier identification and diagnosis of CP would also provide new opportunities for early intervention and targeted rehabilitation services. Abstract : This article is commented on by O'Neill and Godin on page 1346 of this issue.